A Retrospective Global Assessment of Factors Associated With COVID-19 Policies and Health Outcomes - Choi, Angela Jeong; Hean, Andrew C.; Lee, Julia K.; Tran, Nguyen D.; Lin, Tracy Kuo; Apollonio, Dorie E. (Frontiers in Public Health, 2022)
Background The 2019 Global Health Security (GHS) Index measured the capacities of countries to prepare for and respond to epidemics and pandemics. However, the COVID-19 pandemic revealed that GHS Index scores were poorly correlated with ability to respond to infectious disease threats. It is critical to understand how public health policies may reduce the negative impacts of pandemics. Objective To identify non-pharmaceutical interventions (NPIs) that can minimize morbidity and mortality during the COVID-19 and future pandemics, this study examined associations between country characteristics, NPI public health policies, and COVID-19 outcomes during the first year of the pandemic, prior to the introduction of the COVID-19 vaccine. This global analysis describes worldwide trends in policy implementation and generates a stronger understanding of how NPIs contributed to improved health outcomes. Design This cross-sectional, retrospective study relied on information drawn from publicly available datasets through December 31, 2020. Primary and Secondary Outcome Measures We conducted multivariate regressions to examine associations between country characteristics and policies, and policies and health outcomes. Results Countries with higher health service coverage prior to the pandemic implemented more policies and types of policies. Countries with more bordering countries implemented more border control policies (0.78**), and countries with denser populations implemented more masking policies (0.24*). Across all countries, fewer COVID-19 cases and deaths per million were associated with masking (−496.10*, −7.57), testing and tracing (−108.50**, −2.47**), and restriction of movement (−102.30*, −2.10*) policies, with stronger associations when these policies were mandatory rather than voluntary. Conclusions Country characteristics, including health service coverage, number of bordering countries, and population density, may predict the frequency and nature of public health interventions. Countries with higher health service coverage may have the infrastructure to react more efficiently to a pandemic, leading them to implement a greater number of policies. Mandatory masking, testing and tracing, and restriction of movement policies were associated with more favorable COVID-19 population health outcomes. While these results are consistent with existing COVID-19 mathematical models, policy effectiveness depends on how well they are implemented. Our results suggest that social distancing policies were less effective in reducing infectious disease risk, which may reflect difficulties with enforcement and monitoring.